MANAGEMENT OF CREATIVE INDUSTRIES - Semenchuk, Tetiana; Holovii, Oleksandr (Sworld-Us Conference proceedings, 2025)
The article deals with theoretical and practical analysis, as well as substantiates the importance of creative management in the formation and development of creative industries are considered through the prism of cultural approach